1985
DOI: 10.1111/j.1523-536x.1985.tb00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Views of Continuous Electronic Fetal Heart Monitoring and Intermittent Auscultation in a Randomized Controlled Trial

Abstract: We report the views of 200 women interviewed as part of a large randomized controlled trial in a Dublin hospital to compare a policy of continuous intrapartum fetal heart rate monitoring ( E M ) with an alternative policy of intermittent auscultation using a Pinard stethoscope (IA). More women allocated to EFM reported that they felt restricted in their movements than did those allocated to IA. On the other hand, we found no evidence that the method of monitoring either influenced the support that they said th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…However, applying a CTG because a professional cannot be with a labouring woman implies that a professional cannot watch the monitor, therefore reducing any protector effect potentially offered by EFM. In addition, IA allows for close proximity and engagement with women, a view highlighted by women as being very important [37,38]. This might allow for increased communication and afford professionals a greater view of the overall clinical picture.…”
Section: Discussionmentioning
confidence: 99%
“…However, applying a CTG because a professional cannot be with a labouring woman implies that a professional cannot watch the monitor, therefore reducing any protector effect potentially offered by EFM. In addition, IA allows for close proximity and engagement with women, a view highlighted by women as being very important [37,38]. This might allow for increased communication and afford professionals a greater view of the overall clinical picture.…”
Section: Discussionmentioning
confidence: 99%
“…From 14 one‐hour observations during early and late labour, these researchers confirmed that, compared with laywomen’s supportive behaviours, male partners did not stay with their partners all the time. Having fathers leave the labour room at different times may be a source of added stress to the mother, through causing anxiety, fear and feelings of distress at being left alone even for a short period of time ( Garcia et al ., 1985 ). One explanation for fathers’ inconsistent presence during the labour process may be practical reasons, such as the father needing to attend to the family or simply to have a meal.…”
Section: Discussionmentioning
confidence: 99%
“…Complications during delivery, length of labor, pain (21), interventions, use of technology and operative deliveries (22,23), and increasing education (24) can be negatively associated with satisfaction and perception of labor. In contrast, positive correlations have been observed with information, participation in decision making (24), attendance at prenatal classes (25), presence of a support person (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), pain release (26), parity, and social status (20).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have described a wide range of maternal attitudes toward electronic fetal monitoring in labor (17,22,27). Overall satisfaction may not be an indicator for individual aspects of maternal perception, and several factors must be measured (20,28).…”
Section: Discussionmentioning
confidence: 99%